Metodologia para a seleção dos modos de gestão de projetos e inovação - Cararo, Nilton Luiz (2014)
The development of the technological projects into a company, using open innovation, by definition, is a complex task. Attend the customer needs, develop project using partners, reduce risk and cost of the project, using virtual offices and insert new technologies, are some characteristics of open innovation, which make it complex. The development of the projects with those characteristics require an enhanced methodology. The traditional methodologies of project management not support the complex project management, being necessary to use methodologies and specific technics for its management It became important for the company know what kind of project methodology to use and what innovation strategy (open or closed) to use at the development of their projects. The objective of this dissertation is the elaboration of the one methodology to select modes of project management and innovation, in function of customer needs, project specification and requirements, and the capacity of the company to development the project. The data used on the research are secondary, obtained by means of bibliographic research. The methodology used on this dissertation was content analysis, applied on methods and techniques of analysis and scenarios building. The development of scenarios analysis, using methods and techniques proposal at the bibliographic research, had as product the correlation between customer needs, project management (complex and traditional) and innovation (closed and open). The result of this analysis it was a summary frame, indicating the methodology to select innovation strategy and project management. The verification of the consistency of the methodology to select was realized by means of comparison of real projects, developed into an agricultural company.